2013
DOI: 10.1186/2049-2618-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative meta-RNA-seq of the vaginal microbiota and differential expression by Lactobacillus iners in health and dysbiosis

Abstract: BackgroundBacterial vaginosis (BV), the most common vaginal condition of reproductive-aged women, is associated with a highly diverse and heterogeneous microbiota. Here we present a proof-of-principle analysis to uncover the function of the microbiota using meta-RNA-seq to uncover genes and pathways that potentially differentiate healthy vaginal microbial communities from those in the dysbiotic state of bacterial vaginosis (BV).ResultsThe predominant organism, Lactobacillus iners, was present in both condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
226
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(242 citation statements)
references
References 50 publications
(68 reference statements)
7
226
0
9
Order By: Relevance
“…Recent genomic and transcriptomic studies suggest that L. iners is highly adapted to the vaginal compartment (Macklaim et al, 2011). However, it differentially expresses over 10% of its genome in dysbiotic compared with healthy states, with increased expression of a cytolysin, mucin, glycerol transport and related metabolic enzymes (Macklaim et al, 2013). These changes likely result in the production of succinate and other short-chain fatty acids as the end product of metabolism as opposed to lactic acid, leading to an increased vaginal pH.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genomic and transcriptomic studies suggest that L. iners is highly adapted to the vaginal compartment (Macklaim et al, 2011). However, it differentially expresses over 10% of its genome in dysbiotic compared with healthy states, with increased expression of a cytolysin, mucin, glycerol transport and related metabolic enzymes (Macklaim et al, 2013). These changes likely result in the production of succinate and other short-chain fatty acids as the end product of metabolism as opposed to lactic acid, leading to an increased vaginal pH.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriostatic and bactericidal activities are largely due to lactic acid, a product of lactate dehydrogenase enzymes, and to bacteriocins. Studies have shown that stability can be influenced by phage induction (Macklaim et al, 2013;Pavlova & Tao, 2000) but it may also be affected by things that confer resistance to harmful environmental stimuli, such as efflux pumps, or by factors that function in adaptation to changes in nutrient availability. We tested this by examining the whole genomes, the bactericidal activity (lactic acid production) and the stability (phage induction) of strains from women who were predominated by L. crispatus and did not have a history of BV, and comparing these parameters with strains from women with more diverse vaginal microbial profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Excision can be spontaneous or induced by DNA-damaging agents that induce the global SOS stress response. One study indicates that CRISPR-related gene expression is elevated in L. iners during BV, suggesting that CRISPR activity may be a response to a phage-loaded environment (Macklaim et al, 2013). Cigarette smoking, which is associated with BV, may expose the vaginal lactobacilli to chemicals capable of inducing phage (Pavlova & Tao, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that each of the two forms of Gardnerella may be responsible for a different pathogenesis model (Swidsinski et al, 2010). However, as Hickey and Forney (2014) stressed, the correlation between G. vaginalis and BV does not necessarily indicate causation and hence responsibility of this bacterium for either of the two pathogenesis models (Macklaim et al, 2013). The intricate microbial structure of BV is said to result in increased cell lysis and subsequent carbohydrate availability.…”
Section: Pathogenesis Of Bacterial Vaginosismentioning
confidence: 99%